f(n) = f(n+1) +3
f(1) = f(2) +3
f(2) =f(3) +3
f(3) = f(4) +3
So f(1) = f(n) + 3* (n-1)
Put n=4 here so you found
f(1) = f(4) + 3* 3
= 22 +9
=31 ans
hope it helps
The first term according to the recursive sequence is 31
Given the recursive function f(n + 1) = f(n) – 3
If f(4) = 22, hence;
f(3+1) = f(3) - 3
f(4) = f(3) - 3
22 = f(3) -3
f(3) = 22 + 3
f(3) = 25
Also;
f(2+1) = f(2) - 3
f(3) = f(2) - 3
25 = f(2) -3
f(2) = 25 + 3
f(2) = 28
Similarly;
f(1+1) = f(1) - 3
f(2) = f(1) - 3
28 = f(1) -3
f(1) = 28 + 3
f(1) = 31
Hence the first term according to the recursive sequence is 31
Learn more here: https://brainly.com/question/18233843